PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH TERHADAP PENINGKATAN MUTU PENDIDIKAN - Khoerudin, Liana Ariesha; Nugraha, Mulyawan Safwandi; Nasrudin, Endin (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This study aims to determine the effect of the transformational leadership of school principals on improving the quality of education in MTs kecamatan Sukaraja Kabupaten Sukabumi. The research was conducted with a quantitative approach. The sample in this study were all teachers in MTs in the Kecamatan Sukaraja Kabupaten Sukabumi. The data analysis technique used is PLS-SEM. PLS-SEM is a structural equation model to develop or predict an existing theory. The equation model analyzed is the outer model, inner model and hypothesis testing. Based on calculations using SmartPLS 3.0 software. the results of the study show that the transformational leadership of school principals has an effect on improving the quality of education by 0.417 or 41.7%. The implications of the results of this study indicate that to improve the quality of education, it is effective through increasing indicators or dimensions that are still weak on the transformational leadership variable of school principals from this study, namely the idealized influence dimension (exemplary influence). In this case the researcher recommends that the head of the KKMTS Kecamatan Sukaraja Kabupaten Sukabumi should cooperate with the Ministry of Religion of Kabupaten Sukabumi to carry out the madras technical guidance program, in order to improve the professionalism and personality competence of the madarsa head, as well as be a good role model for the madrasah community and the surrounding community. So that school principals are aware that their personal competence can be further improved. The results of testing the hypothesis showed that there was a significant influence between the school principal's transformational leadership on improving the quality of education (t-statistic 4.242 and p values <0.05)